Application of the Metaphor Architecture Theme in the Design of the Institute of Marine Sciences and Fisheries in Sibolga City (International Journal of Architecture and Urbanism, 2023)
The Sibolga Institute of Marine and Fisheries Science design is a college plan that organizes academic and vocational education in groups of science, technology, and arts disciplines focused on the marine and fisheries sector in Sibolga City. This design is reviewed based on the great potential of fisheries and marine in the Sibolga area. However, it has not been appropriately managed and optimally so far. In addition, the Sibolga Institute of Marine and Fisheries Science design is expected to answer the problem of limited educational facilities, especially in the scope of marine and fisheries science in Sibolga City. The study employs a descriptive qualitative method. Site survey and literature studies on metaphoric architecture principles serve as the primary data collection technique in the study. The application of a design with a symbolic architectural theme is expected to represent the function of the building. Therefore, observers and building users will have their ideas and impressions of the activities that occur in the building through the shape of the mass and the facade of the building. This study can benefit future studies that attempt to apply metaphoric architecture in their design.